Factors influencing of quality of life in adolescent idiopathic scoliosis. (December 2022) - Kaya, Mehmet Hanifi; Erbahçeci, Fatih; Alkan, Halil; Kocaman, Hikmet; Büyükturan, Buket; Canlı, Mehmet; Büyükturan, Öznur
Abstract: Background: Adolescent idiopathic scoliosis (AIS) is the lateral and horizontal deformity of the vertebral column which occurs idiopathically during adolescence. The aim of this study is to identify independent predictors of quality of life in AIS patients. Methods: In total, 31 adolescent patients diagnosed with AIS aged between 10 and 18 years old were included in the study. The scoliosis severity was determined for each patient according to the Cobb method, and their scoliosis perception using the Walter Reed Visual Assessment Scale, a pain assessment was conducted based on the Visual Analog Scale, quality of life using the Scoliosis Research Society-22 questionnaire, and depression level according to the Children's Depression Scale. Multiple Linear Regression analysis was then performed in order to determine the independent determinants of health-related quality of life. Findings: According to the Linear Regression analysis results, children's depression scale, walter reed visual assessment scale, cobb, and anterior trunk rotation explained 52.7% of the variance as independent determinants of SRS-22. Interpretation: The study examined the determinants affecting the quality of life in AIS patients. The results of the study showed that scoliosis severity, perception of cosmetic deformity, degree of rotation, and depression level to be predictors of quality of life in AIS patients. "This trail registered with NCT05242601." Highlights: Quality of life, Cobb, perception of deformity and depression are related in AIS. Quality of life in AIS is affected by different parameters. Multiple factors may be independent predictors of quality of life in AIS.